Clinical Decision Support: Strategies for Success - Mohamed Khalifa (2014)
Clinical Decision Support Systems (CDSS) are considered essential tools of evidence-based medicine. These systems provide physicians, caregivers and also patients with clinical knowledge needed and patient or disease specific information to help them make effective decisions that would enhance patient care and improve clinical outcomes. The lack of well-described success factors is the main challenge facing design, development and implementation of CDSS. We need to learn more about the factors that can help in increasing usability and acceptance. The medical informatics department at King Faisal Specialist Hospital and Research Center, Jeddah, Saudi Arabia worked on identifying and describing best strategies and requirements for success of CDSS building a detailed plan for development and implementation. The explored recommendations were categorized into ten main topics that should be addressed. These include the right content of CDSS, delivering valid and reliable information, delivering simple messages, providing users with references, saving users' time, integrating with clinical workflow, improving system response and speed, adopting active and passive alert mechanisms, integrating with other hospital information systems (HIS) and proper management of CDSS knowledge.